دراسة منهجية لمقررات العقيدة الأشعرية: أم البراهين نموذجًا: (Systematic Study of Ash'ari Doctrine Courses: Umm al-Barahin as a Model) - Saged, Ali Ali Gobaili; Syed Abdul Rahman, Syed Mohammad Hilmi; Alaa Eddine, Ben Kherif (Online Journal of Research in Islamic Studies, 2024)
This study aims to define and adjust some of the terms related to Islamic creed topics and to explain the ideological circumstances that influenced the construction and formulation of definitions, as well as to clarify the methodology upon which the most important text of Ash'ari creed is based, namely Umm al-Barahin by Imam al-Sanusiy through elucidating the general frameworks and paths that al-Sanusiy formulated to establish this unique Sunni creed. The researcher has resorted to an inductive approach to achieve these objectives, tracing the Ash'ari school back to the era in which Umm al-Barahin was composed and to the analytical approach where he interprets and deduces the text's vocabulary back to its origins in the Quran and the Sunnah, in accordance with the decisive minds. Among the conclusions drawn, it appears that the term "creed" is a comprehensive and definitive concept that prevents differences of opinion, and that the Ash'ari school is a comprehensive structure and extension of what the predecessors of this Muslim nation adhered to. The foundations of this Sunni approach are manifested in the text of Umm al-Barahin through the combination of certainty from revelation and reason, the encouragement of contemplation, the exaltation of the truth above resemblance to creation, avoidance of excommunication, reliance on interpretation where needed, and submission where language and reason fall short. The scientific value of the research lies in clarifying the reality of Ash'ari creed and explaining the cognitive foundations upon which it is based through their established texts.